2013
DOI: 10.3109/02713683.2013.783079
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of TUNEL-labeling in the Rat Lens AfterIn VivoExposure to Just Above Threshold Dose UVB

Abstract: Close to threshold dose of UVB induces TUNEL-labeling that peaks in the time window 5-120 h after exposure to UVB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…17 However, in this study, we found TUNEL staining at 5 hours after exposure in the cornea. This finding is consistent with threshold doses of UVR in the cornea and lens in previous studies.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…17 However, in this study, we found TUNEL staining at 5 hours after exposure in the cornea. This finding is consistent with threshold doses of UVR in the cornea and lens in previous studies.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, to detect spatial resolution, we chose the TUNEL method, as has been used in other studies on detection of apoptosis in the cornea. 2,8,12,[17][18][19] UVR in the 300-nm wavelength region was chosen because it has been shown in vivo to be the most harmful waveband for lens epithelial cells in rats and rabbits. 1,9 Little is known about corneal UVR-300-nm exposure.…”
Section: Discussionmentioning
confidence: 99%
“…UV light has been shown to cause apoptosis in lens cells and in whole lenses (21,22,(27)(28)(29) and because UV light exposure is associated with cataract formation (18 -20), we sought to determine the effect of UVA light on the subunits of the integrin ␣V␤5 receptor and on the process of lens cell phagocytosis of apoptotic debris. To test this, human SRA 01/04 lens epithelial cells were exposed to UVA light using a UVA LED array.…”
Section: Uva Treatment Of Lens Epithelial Cells Results In Loss Of Bomentioning
confidence: 99%
“…Most of the UV light transmitted to the lens is therefore UVA light; this is primarily absorbed by the anterior lens epithelium, and long term UVA exposure is believed to contribute to lens damage (24,83,84). UV light exposure of lens epithelial cells is associated with apoptosis of lens epithelial cells (21,22,(27)(28)(29) and human cataract formation (18 -20); however, the mechanisms used by lens epithelial cells to deal with the downstream effects of UV light and other insults, i.e. apoptosis and accumulation of apoptotic debris to ensure epithelial cell homeostasis and lens transparency, remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation